TREATMENT PLANNING SYSTEM (TPS) KANKER PAYUDARA MENGGUNAKAN TEKNIK 3DCRT - Wida Farhiyati; Rinarto Subroto; I Wayan Ari Makmur; Nurul Qomariyah; Rahadi Wirawan (ORBITA: Jurnal Kajian, Inovasi dan Aplikasi Pendidikan Fisika, 2020)
ABSTRAKPenelitian ini bertujuan untuk mengevaluasi hasil  simulasi TPS teknik 3DCRT pada  kasus kanker payudara agar sesuai dengan standar yang diizinkan International Commission on Radiation Units and Measurements (ICRU). Proses TPS menggunakan program Eclipse dengan algoritma Anisotropic Analytical Algorithm. Kurva histogram dosis volume kumulatif 3DCRT dianalisis untuk mendapatkan dosis radiasi yang diterima organ at risk (OAR) paru-paru kiri, paru-paru kanan dan jantung. Hasil TPS  menunjukkan dosis yang diterima OAR berada di bawah batas ambang yang ditentukan yaitu paru-paru kiri dengan mean dose 54,7 cGy yang melingkupi volume 1238,5 cm3 dan pada paru-paru kanan dosis mean dose 2113,2 cGy melingkupi volume 1474,5 cm3 serta pada jantung mean dose 96,5 cGy melingkupi volume 175,5 cm3. Simulasi TPS yang dilakukan berhasil mendapatkan data perencanaan penyinaran  kasus kanker payudara yang memenuhi syarat dosis relatif yang melingkupi volume PTV yang diizinkan ICRU (volume terlingkupi 95%-107%) yaitu besarnya dosis relatif untuk target sebesar 95% yang melingkupi 95,5% volume target. Kata kunci: radioterapi, TPS, dosis, PTV, OAR. ABSTRACTThis study objective is to evaluate the simulation results of the 3DCRT technique TPS  in breast cancer cases to conform to the standards permitted by the International Commission on Radiation Units and Measurements (ICRU). The TPS process uses the Eclipse program with the Anisotropic Analytical Algorithm algorithm. The 3DCRT cumulative dose-volume histogram curve was analyzed to obtain the absorbed dose received by the organ at risk (OAR) of the left lung, right lung and heart. The TPS results show that the dose received by OAR was below the prescribed threshold of the left lung with a mean dose of 54.7 cGy covering a volume of 1238.5 cm3 and to the right lung the mean dose of 2113.2 cGy surrounding the volume of 1474, 5 cm3 and at the heart the mean dose of 96.5 cGy covers a volume of 175.5 cm 3. TPS simulation carried out successfully obtained data on the planning of radiation from breast cancer cases that met the relative dosage requirements that covered the volume of PTV permitted by ICRU (95% -107% enclosed volume), that is, the relative dose for the target of 95% which covered 95.5% of the target volume. Keywords: radiotherapy, TPS, dose, PTV, OAR.